2015
DOI: 10.1177/0021998315595113
|View full text |Cite
|
Sign up to set email alerts
|

Technological properties of thermoplastic composites filled with fire retardant and tea mill waste fiber

Abstract: In this study, physical, mechanical, thermal, fire and biological properties of thermoplastic composites filled with fire retardant and tea mill waste fiber were investigated. The composites produced with the extrusion method were accomplished by using tea mill waste fiber as lignocellulosic materials and high-density polyethylene and polypropylene as thermoplastic polymer. Aluminum trihydrate and zinc borate were incorporated with different contents into polymer matrix for improving fire properties of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…Similar results, such as decreasing of the impact strength of composites with increasing MCC loading, were also observed in other studies (Zaini et al 1996;Bengtsson and Oksman 2006;Kiziltas et al 2010;Zulkifli et al 2015). Such findings can be attributed to an increase in its brittleness due of addition of the high amounts of MCC into the polymer matrix (Cavdar et al 2015). Kiziltas et al (2010) reported that polymer mobility increases with increasing MCC content and leads to lower impact strength.…”
Section: Mechanical Propertiessupporting
confidence: 84%
See 1 more Smart Citation
“…Similar results, such as decreasing of the impact strength of composites with increasing MCC loading, were also observed in other studies (Zaini et al 1996;Bengtsson and Oksman 2006;Kiziltas et al 2010;Zulkifli et al 2015). Such findings can be attributed to an increase in its brittleness due of addition of the high amounts of MCC into the polymer matrix (Cavdar et al 2015). Kiziltas et al (2010) reported that polymer mobility increases with increasing MCC content and leads to lower impact strength.…”
Section: Mechanical Propertiessupporting
confidence: 84%
“…MCC did not seriously affect tensile strength of the composites, while nutshell resulted in a minor decrease in tensile strength. This can be related to differentiation between the size of MCC (40 µm) and nutshell fiber (0.5 mm) (Cavdar et al 2015). As also shown in Fig.1, the variance analysis indicated that MCC loading had a significant effect on tensile strength and tensile modulus.…”
Section: Mechanical Propertiesmentioning
confidence: 56%
“…Elongation at break was sharply decreased when cupula fiber filled in the polymer matrix. It is known that natural fibers make the composites more brittle with addition in polymer matrix because the fibers have higher brittleness and rigid than the HDPE . In the light of these results, the cupula fiber filled r‐HDPE composites produced with alkali treated fibers at 40 wt% loading have optimum mechanical properties.…”
Section: Resultsmentioning
confidence: 91%
“…Hence, the reinforced composite becomes more rigid then neat polymer matrix. [ 6, 46, 47 ] The increase of rigidity in the composites was not observed when AKD added in the polymer matrix. FMOE of the filler reinforced composites decreased in the presence of AKD.…”
Section: Resultsmentioning
confidence: 99%